Analysis of Clean Water Needs in Soya Village, Sirimau District, Ambon City By Using EPANET 2.2 Software - Novita Irma Diana Magrib; Charles Johandersson Tiwery (Tibuana, 2023)
Clean water is one of the basic human needs that is needed on an ongoing basis. The use of clean water is very important for household consumption, industrial needs and public places. Because of the importance of the need for clean water, it is only natural that the clean water sector is given top priority for handling because it involves the lives of many people. Fulfilling the need for clean water is highly dependent on the availability of clean water sources, which can be obtained from groundwater and surface water, which can be provided from rivers, springs, weirs and reservoirs/reservoirs. The method of collecting and analyzing the data used in this study was to conduct a survey at the research location to review and see directly the conditions of the research location, then create a piping system that is suitable for the research location, after that calculate population projections and calculate the appropriate water requirements for the project. piping system, and using EPANET 2.2 software to analyze the feasibility of the piping system based on population and water demand. Based on calculations and modeling using Epanet 2.2 software for the distribution of piping network systems in Soya Village, Sirimau District, Ambon City, several conclusions can be drawn, namely the need for clean water needed by the residents of Waisamu Village is 44.45 liters/second, with the total water requirement then modeling the distribution of the piping network system is made using Epanet 2.2 software, and the results obtained are Run Successful, which means the distribution of the piping system runs 100%.